Rapid hydrothermal synthesis route for nanocrystalline SrZrO3 using reactive precursors - Athawale, Anjali A.; Chandwadkar, Asha J.; Karandikar, Prashant R.; Bapat, Malini S. (Materials Science and Engineering B-Solid State Materials for Advanced Technology, 2005)
Synthesis of nanocrystalline, orthorhombic (space group Pnma) SrZrO3 was achieved using appropriate molar proportions of nitrate salts of strontium and zirconium as precursors. Formation of SrZrO3 (SZ) was facilitated hydrothermally in time period as less as half-an-hour, in aqueous medium with alkaline pH as confirmed by XRD. Sample characterization was performed by FT-IR spectroscopy; powder XRD, SEM, TEM and DSC. The results have been explained by proposing a suitable reaction mechanism based on the step-wise analysis of the reaction intermediates using FT-IR as well as XRD. A double cation hydroxide composite formation is anticipated that under hydrothermal conditions results in the formation of SrZrO3. Morphology of the samples was determined with the help of SEM and TEM. The particle size distribution as seen from the TEM micrograph lies in the range of 15-25 nm. Heats of reaction for different decomposition steps were obtained by DSC. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: Ceramics; Crystallization; diffraction; Electron microscopy; infrared spectroscopy

Studies on characterization of nano CaCO3 prepared by the in situ deposition technique and its application in PP-nano CaCO3 composites - Mishra, Satyendra; Sonawane, S. H.; Singh, R. P. (Journal of Polymer Science Part B: Polymer Physics, 2005)
The elegant approach of in situ deposition technique was used for the synthesis of nano CaCO3 the nanosize of particles was confirmed by the X-ray diffraction (XRD) technique. Differential scanning calorimetry (DSC) was used for determination of the enthalpy. The nano CaCO3 polypropylene (PP) composites were prepared by taking 2 and 10 wt % of different nanosizes (21-39 nm) of CaCO3. Conversion of the alpha phase to beta was observed in the case of 2 wt % of a 30-nm sized amount of CaCO3 in a PP composite. The decrement in DeltaH and percent. crystallinity, as well as the increment in melt temperature were recorded for 6 wt % nano CaCO3 with a decrease in nanosize from 39 to 21 nm. The increment in tensile strength with an increase in the amount of nano CaCO3 was observed, and the tower particle size shoved Greater improvement. The improvement in thermal and mechanical properties is because of the formation of a greater number of small spherulites uniformly present in the PP matrix. (C) 2004 Wiley Periodicals, Inc.
Keywords: Crystallization; DSC; mechanical and thermal properties; nano CaCO3; polypropylene; XRD

Synthesis and characterization of poly(higher-alpha-olefin)s with a nickel(alpha-diimine)/methylaluminoxane catalyst system: effect of chain running on the polymer properties - Subramanyam, Ummadisetty; Sivaram, Swaminathan (Journal of Polymer Science Part A-Polymer Chemistry, 2007)
Homopolymerization of octadecene-1 at different reaction conditions has been studied. Significant chain running can be seen at higher polymerization temperatures. Interestingly, insertion of octadecene-1 into a sterically hindered nickel-cation/carbon (secondary) bond is observed. The microstructure of the polymer was established using NMR spectroscopy. The effects of chain running on polymer melting, crystallization behavior, and dynamic mechanical thermal properties were studied using DSC and DMTA. The extent of chain running (i.e., 2 omega-, 1,omega-enchainments) decreases with an increase in the carbon number of alpha-olefins. (c) 2006 Wiley Periodicals, Inc.
Keywords: chain running; Crystallization; glass transition; melt transition; nickel (alpha-diimine); NMR; poly(alpha-olefin)s

Studies on the effect of glass transition on the crystalline transition in syndiotactic polystyrene - solvent complexes - Naidu, Sudhakar; Ramesh, N. C. (Macromolecular Symposia, 2008)
Amorphous syndiotactic polystyrene (sPS) was crystallized at room temperature in Norbornadiene (bicyclo[2,2,1]-hepta-2,5-diene), Mesitylene (1,3,5-Trimethyl benzene), 3-Carene (3,7,7-trimethyl bicyclo[4,1,0]hept-3-ene) and DMN (1,4-Dimethylnaphthalene) to form the sPS-solvent complex (h form) with respective solvent molecules. In situ HTFTIR studies showed that the delta form to gamma form transformation temperature occurs well below the glass transition temperature of sPS, which is depressed due to the presence of solvent in the amorphous phase; higher the solvent content in the complex, lower the transition temperature. Glass transition temperatures determined by Modulated differential scanning calorimetry (MDSC) coincide with the transition temperatures, indicating that the delta form transforms into gamma form at the glass transition temperature for these complexes. Such a behavior is very different from the behaviour of the sPS- solvent complexes formed by dichloromethane, chloroform, toluene, o-dichlorobenzene, decalin (cis-trans) etc. and for these complexes the transition occur well above the T(g).
7th Conference on Polymer Solvent Complexes and Intercalates, Marrakech, MOROCCO, MAY 21-23, 2008
Keywords: Crystallization; glass transition; infrared spectroscopy; Syndiotactic polystyrene

Micro-/meso-porous stannosilicate composites (Sn-MFI/MCM-41) via two-step crystallization process: process parameter-phase relationship - Niphadkar, Prashant S.; Garade, Ajit C.; Jha, Ratnesh Kumar; Rode, Chandrashekhar V.; Joshi, Praphulla N. (Microporous and Mesoporous Materials, 2010)
Sn-MFI/MCM-41 composite material was successfully synthesized by monitoring the re-crystallization time in a simple two-step crystallization process. The length of period allowed for the recrystallization of the precursor species was found to be a controlling factor to achieve either the end members viz. Sn-MCM-41 and Sn-MFI or Sn-MFI/MCM-41 composite material. Powder XRD, FTIR, SEM, TEM, nitrogen sorption measurement, DRUV-vis and hydroxyalkylation of p-cresol reaction were used as the characterization tools. Attempts were also made to establish the relationship between type of phase formed and the process parameters such as aging time, re-crystallization temperature, time and molar ratios of TPAOH/SiO(2), CTMABr/SiO(2) and SiO(2)/SnO(2) in the gel. (C) 2010 Elsevier Inc. All rights reserved.
Keywords: composites; Crystallization; Micro-/meso-porous stannosilicate; p-Cresol hydroxyalkylation; Sn-MCM-41; Sn-MFI

Crystalline xylitol production by a novel yeast, pichia caribbica (HQ222812), and its application for quorum sensing inhibition in gram-negative marker strain chromobacterium violaceum CV026 - Mukherji, Ruchira; Joshi-Navare, Kasturi; Prabhune, Asmita (Applied Biochemistry and Biotechnology, 2013)
Xylitol, a sugar alcohol, is fast gaining ground over other artificial sugar substitutes owing to its advantageous properties. Xylitol is a safer alternative for diabetics because of insulin-independent metabolism. It has beneficial properties suitable to form an important part of odontological formulations. Conventional commercial production of xylitol involves harsh chemical method operating at high temperature and pressure. Thus, microbial production of xylitol is preferred over chemical method, and yeasts have been extensively exploited for this purpose. In the present manuscript, quantitative production of xylitol from d-xylose with the yield of 0.852 gm/gm and volumetric productivity of 1.83 gm/l/h in crystalline form, using novel yeast Pichia caribbica is reported. Also, a mild, safe procedure for product extraction is described. The ability of xylitol to act as a quorum sensing antagonist in gram-negative marker strain Chromobacterium violaceum CV026 has been demonstrated for the first time.
Keywords: Crystallization; CV026; Pichia caribbica; Quorum sensing antagonist; xylitol

Crystallization: key thermodynamic, kinetic and hydrodynamic aspects - Vedantam, Sreepriya; Ranade, Vivek V. (Sadhana-Academy Proceedings in Engineering Sciences, 2013)
Crystallization is extensively used in different industrial applications, including the production of a wide range of materials such as fertilizers, detergents, food and pharmaceutical products, as well as in the mineral processing industries and treatment of waste effluents. In spite of the wide-spread use of crystallization, a clear understanding of the thermodynamic, kinetic and hydrodynamic aspects of the design methodologies are not yet well established. More often than not crystallization is still considered an art especially in fine-chemicals, pharmaceuticals and life-sciences sector. It is essential to understand and relate key thermodynamic, kinetic and hydrodynamic aspects to crystallizer performance, not just in terms of yield but also in terms of product quality (characterized by particle size distribution, morphology, polymorphism and the amount of strain as well as the uptake of solvent or impurities in the crystal lattice). This paper attempts to do that by critically reviewing published experimental and modelling studies on establishing and enhancing state-of-the-art thermodynamic, kinetic and hydrodynamic aspects of crystallization. Efforts are made to discuss and raise points for emerging modelling tools needed for a flexible design and operation of crystallizers and crystallization processes that are needed to meet the ever increasing demand on precise product specifications. Focus is on bringing out the trends which can be used as perspectives for future studies in this field.
Keywords: CFD; Crystallization; growth; Nucleation; polymorphism; supersaturation

Crystallization kinetics of Sn-MFI molecular sieve formation by dry gel cross mark conversion method - Niphadkar, P. S.; Tangale, N. P.; Joshi, P. N.; Awate, S. V. (Microporous and Mesoporous Materials, 2013)
The conversion of amorphous stannosilicate dry gel into crystalline molecular sieve with MFI structure (Sn-MFI) was achieved by dry gel conversion (DGC) method at 413, 443 and 473 K. For comparison purpose, Sn-MFI molecular sieve with similar SiO2/SnO2 mole ratio was also obtained by hydrothermal crystallization route. Crystallization curves were established by conducting time dependant studies on progressive crystallization processes for both the systems. The values of activation energy of nucleation (E-n), activation energy of crystallization (E-c), and their pre-exponential factors (InA(n), InA(c) respectively) were calculated from Arrhenius plots. Compared to the hydrothermal method, shorter induction period was observed when DGC method was employed. Both the E-n (49.70 kJ/mol) and E-c (52.82 kJ/mol) for DGC method were found to be lower than that of the E-n (55.70 kJ/mop and E-c (60.23 kJ/mol) for hydrothermal method. The kinetics parameters viz. K and q were derived from kinetic expressions and DGC method showed higher value of K and lower value of q compared to hydrothermal crystallization method at identical temperature. Various DGC method parameters such as water content at the bottom of autoclave and SiO2/SnO2 mole ratio have shown the influence on the kinetics of crystallization of Sn-MFI. (C) 2013 Elsevier Inc. All rights reserved.
Keywords: Crystallization; DGC; kinetics; Nucleation; Sn-MFI

Ultrasound promoted efficient and green protocol for the expeditious synthesis of 1, 4 disubstituted 1, 2, 3-triazoles using Cu(II) doped clay as catalyst - Dar, Bashir Ahmad; Bhowmik, Amrita; Sharma, Amit; Sharma, Parduman R.; Lazar, Anish; Singh, A. P.; Sharma, Meena; Singh, Baldev (Applied Clay Science, 2013)
Cu(II) doped clay catalyst has been prepared by an easy technique from inexpensive starting materials and investigated for the one pot synthesis of 1, 4-disubstituted 1, 2, 3-triazoles via Huisgen [3 + 2] cycloaddition under ultrasonic irradiation at room temperature. The catalyst is highly active, selective, and stable and can be reused several times. The prepared catalyst has been characterized by XRD, BET-SA, H-2-TPR, SEM and XPS techniques. This transformation is fast, efficient and does not require nitrogen atmosphere or anoxic conditions and additive. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: Catalyst support; Copper catalyst; Crystallization; selectivity; Sustainability

Effect of ionic interactions on crystallization of star telechelic poly (L-lactide) ionomers - Kulkarni, Amruta (Polymer, 2022)
Effect of ionic interactions on crystallization properties of star telechelic poly(L-lactide) ionomers was studied by performing isothermal crystallization experiments. We report a comparison between star PLLA and star telechelic PLLA ionomer. It was evident that the ionic interactions in the ionomer affected the crystallization rate as well as modified the spherulitic morphology. Employing Avrami analysis on the isothermal crystallization data we show that star PLLA shows faster crystallization at higher temperatures (closer to melting point) than the star PLLA ionomer. However, a reversal of this trend in crystallization is observed at lower temperatures (closer to glass transition temperature). The origin of high temperatures behaviour comparison is explained in terms of the higher secondary nucleation barrier for ionomers using the famous Lauritzen- Hoffman secondary nucleation theory. However, we point out that the assumption of equal diffusion barrier in this theory limits its range of applicability. In order to explain the low temperature behaviour, we invoke the activation energy comparison in PLLA and ionomer using rheological studies. We show that although the presence of ions in the polymer impede the secondary nucleation process, its effect is only observed at higher temperatures.
Keywords: Crystallization; Ionomer; Poly( L -lactide); Star polymer; Telechelic

Enhancing the crystallization kinetics and mechanical properties of poly(lactic acid) blends for 3D printing application - Kothavade, Premkumar; Yadav, Prashant; Gopal, Animesh; Pol, Harshawardhan; Kafi, Abdullah; Bateman, Stuart; Shanmuganathan, Kadhiravan (ACS Applied Polymer Materials, 2024)
3D printing of poly(lactic acid) (PLA) blends has been attempted to resolve issues such as inherent brittleness and slow crystallization rate of PLA. However, a persistent challenge remains in the form of phase separation or gradual migration of the blended soft polymer or plasticizers. To simultaneously enhance the miscibility of the blends and toughness of 3D-printed parts, a triblock copolymer PLA-PEG-PLA was synthesized and blended with PLA in varying proportions (5, 10, 15, and 20 wt %). Blending only 10-20 wt % low molecular weight PLA-PEG-PLA into PLA yielded a miscible blend that showed a 45-fold increase in elongation at break and a 23-fold enhancement in toughness over neat PLA. Scanning electron microscopy (SEM) images of fractured cross sections revealed a brittle to ductile transition in 3D-printed PLA/PLA-PEG-PLA samples. Isothermal crystallization studies and data analysis using the Avrami equation showed an enhancement in the crystal growth rate and overall rate of crystallization. The blends achieved half of their crystallinity in approximately 3 min, a significant improvement over the 9 min required by PLA alone. This underscores the efficiency of our approach. This was also evident in the spherulite growth of 3D-printed PLA and mPLA blends when examined using polarized optical microscopy (POM). To the best of our knowledge, this is the first report exploring the use of blends that include PLA and low molecular weight PLA-PEG-PLA triblock copolymers for 3D printing applications.
Keywords: Crystallization; FFF 3D printing; PLA-PEG-PLA triblock copolymer; poly(lacticacid); toughness

Desymmetrization of myo-inositol - Patil, Nivedita T.; Patil, Madhuri T.; Gonnade, Rajesh G.; Shashidhar, Mysore S. (Carbohydrate Research, 2025)
Chemistry and biology of phosphoinositols have been intensely investigated areas of research over the last 4-5 decades due to their involvement in cellular signal transduction pathways. Efficient laboratory synthesis of enantiomeric derivatives of inositols was a central issue since they were required for the delineation of the myo-inositol cycle as well as for the total synthesis of polyol based natural products and their derivatives. This essentially meant the development of competent methods for the desymmetrization of myo-inositol leading to the preparation of enantiomeric O-substituted derivatives of myo-inositol. This was approached by: the classical resolution methods involving separable diastereomers, the chiral pool synthesis, enzyme catalysis, asymmetric catalysis and preferential crystallization of enantiomers in a racemic conglomerate. This review summarizes results obtained in author's laboratory, as well as those reported in the literature on attempts at desymmetrization of myo-inositol.
Keywords: Conglomerate; Crystallization; Cyclitol; Enantiomers; Inositol; Lipid

Thermal properties of polyethylene-grafted sheetlike silsesquioxanes - Sharma, Vivek; Paulbudhe, Uday; Gupta, Poonam; Zalte, Akshat Shirish; Chikkali, Samir H.; Kumaraswamy, Guruswamy (ACS Applied Polymer Materials, 2025)
Polyethylene-grafted layered silsesquioxanes, termed polyethylene-clays (PEC), are nanocomposites comprising polyethylene chains tethered to inorganic sheets with a phyllosilicate-like structure. Here, we report that these nanocomposites show two-stage crystallization on cooling, qualitatively different from previous reports on polyethylene nanocomposites. We employ differential scanning calorimetry (DSC) and small-angle X-ray scattering (SAXS) to study the melting and crystallization of PEC. End tethering of the polyethylene chains to a nanosheet strongly influences the manner in which PEC crystallizes from the melt on cooling. PEC exhibits two-step crystallization, characterized by a sharp high-temperature exotherm, followed by a broader exotherm at lower temperatures, in contrast to a single sharp exotherm for neat polyethylene. SAXS indicates that lamellar stacks form at high temperatures and that the low-temperature exotherm corresponds to the formation of additional lamellae and their insertion within these stacks. PEC exhibits lower peak melting temperature, lower crystallinity, and a wider melting range relative to polyethylene. We show that the progress of crystallization of PEC is determined by its ultraslow relaxation dynamics. In contrast, PEC in xylene solution exhibits a significantly shorter relaxation time than the melt PEC. Such systems exhibited a single exotherm on cooling and SAXS structure factor peaks with peak positions in a ratio of 1:2. We hypothesize that the high melt viscosity inhibits the crystallization-induced decrease in the specific volume of PEC, resulting in tensile internal stresses that determine the observed thermal behavior.
Keywords: clay; Crystallization; Nanocomposite; Polyethylene; silsesquioxane

Upcycling of postconsumer recyclate polypropylene into low warping and high toughness 3D printable filaments - Gopal, Animesh; Patil, Prashant; Pol, Harshawardhan; Shanmuganathan, Kadhiravan (ACS Applied Polymer Materials, 2025)
Polypropylene (PP) is widely used in commodity applications owing to its chemical stability, mechanical properties and low cost. However, almost 50% of the produced PP ends up as postconsumer waste (PCW) within a short period of usage. Being a non-biodegradable polymer, recycling PCW PP is important to mitigate plastic waste in landfills. Nonetheless, recycling or upcycling postconsumer recyclate (PCR) PP into valuable resources without deterioration in physical and mechanical properties is a challenge. This report presents an approach to upcycle PCR polypropylene (rPP) into high quality 3D printing filament that not only prints with very low warpage but with significantly high elongation at break and toughness. Incorporation of poly(butylene adipate-co-terephthalate) (PBAT) along with maleic anhydride grafted polypropylene (MAPP) in specific proportions led to a significant enhancement in mechanical properties, miscibility, crystallization behavior, and 3D printability. rPP/PBAT blends with 20 wt % PBAT and 10 wt % MAPP exhibited a 62-fold enhancement in elongation at break over rPP (from 1.88 to 118.29%) and a 72-fold increase in toughness (from 2 to 143.60 kJ/m3) with almost similar tensile strength. The final printed components had better layer adhesion and structural stability with a dramatic decrease in warpage, from 25.82% for pristine rPP to only 7.86% for rPP/PBAT blend. Isothermal crystallization studies and data analysis using the Avrami equation showed that crystallization half-time (t 1/2), which measures the duration needed for half of the total crystallinity to form, increased from 12.6 s for rPP to 66 s for the rPP/PBAT blend. This report demonstrates an approach to upcycle PCR PP, a positive step toward realizing the goals of circular economy and sustainable additive manufacturing.
Keywords: Crystallization; FFF 3D printing; polypropylene/poly(butylene adipate-co-terephthalate)blends; toughness; warpage

Low warping and high toughness recycled high density polyethylene for fused filament fabrication 3D printing - Gopal, Animesh; Chaubal, Aman; Shanmuganathan, Kadhiravan (Polymer Engineering and Science, 2026)
The incorporation of recycled polymers in additive manufacturing offers a sustainable pathway to reduce plastic waste while enabling cost-effective production of functional components. High-density polyethylene (HDPE) is an attractive material for 3D printing owing to its low density, chemical resistance, and recyclability. However, its high crystallinity and tendency to shrink often lead to warpage and poor interlayer adhesion. This study proposes a blend-based strategy to overcome these limitations by incorporating tough linear low-density polyethylene (LLDPE) into recycled HDPE (rHDPE). The blends were prepared through melt extrusion, and their mechanical, rheological, morphological, and thermal properties, and 3D printability were comprehensively evaluated. rHDPE/LLDPE blends showed a remarkable improvement in elongation at break (from 3.2% to 84.7%) and toughness without compromising tensile strength. Addition of LLDPE led to a moderate reduction in the crystallinity of rHDPE/LLDPE blends (from 69% to 52.5%) but a significant reduction in the warpage of 3D printed samples (from 27% to 7.6%). Rheological and morphological analyses confirmed good miscibility and uniform phase distribution in the blends, with increasing LLDPE content enhancing complex viscosity and melt elasticity. Overall, the rHDPE/LLDPE blends exhibit superior mechanical performance and reduced warpage, establishing their potential for FFF 3D printing applications.
Keywords: Crystallization; FFF 3D printing; high-density polyethylene blends; Recycling; toughness; warpage